What about the role of the cerebellum in music-associated functional recovery? A secondary EEG analysis of a randomized clinical trial in patients with Parkinson disease. (March 2022) - Naro, Antonino; Pignolo, Loris; Bruschetta, Daniele; Calabrò, Rocco Salvatore
Abstract: Rhythmic Auditory Stimulation (RAS) has been shown to be of help in an effective gait training of people with idiopathic Parkinson's disease (PD). The cerebellum may play an important role in RAS aftereffects by compensating the detrimental internal clock for automatic and rhythmic motricity. However, the neurophysiological mechanisms underlying RAS aftereffects are still poorly understood. In the present study, we tested the contribution of the cerebellum to RAS-based gait training aftereffects in people with PD by examining cerebellum-cerebral connectivity indices using standard EEG recording. We enrolled 50 patients with PD who were randomly assigned to two different modalities of treadmill gait training using GaitTrainer3 with and without RAS (non_RAS) during an 8-week training program. We measured clinical and kinematic gait indices and electrophysiological data (standard EEG recording during walking on GaitTrainer3) of both the gait trainings. We found that the greater improvement in gait performance following RAS than non_RAS training, as per clinical and kinematic assessment, was paralleled by a more evident reshape of cerebellum-brain functional connectivity with regard to specific brain areas (pre-motor, sensorimotor and temporal cortices) and gait-cycle phases (mainly 25–75% of the gait cycle duration). These findings suggest that the cerebellum mediates the reshape of sensorimotor rhythms and fronto-centroparietal connectivity in relation to specific gait-cycle phases. This may be consistent with a recovery of the internal timing mechanisms generating and controlling motor rhythmicity, eventually improving gait performance. The precise definition of the cerebellar role to gait functional recovery in people with PD may be crucial to create patient-tailored rehabilitative approaches. Highlights: Rhythmic Auditory Stimulation (RAS) helps for an effective gait training in PD. The cerebellum may compensate for the loss of automatic and rhythmic motricity. RAS reshapes the cerebellum-brain functional connectivity with regard to specific gait-cycle phases. RAS may induce a recovery of the internal timing mechanisms generating and controlling motor rhythmicity.